The Suzhou Classical Gardens: An Analysis of the GardeningIdeas of Cultural Ecology and Humanity Restoration - Xu, Yukai; Suwanthada, Prathabjai (Journal of Roi Kaensarn Academi, 2024)
Chinese classical gardens are the precious heritage of human culture, the materialized history and the personified carrier. They are famous for their natural landscape style. Chinese classical gardens are mostly concentrated in the south of the Yangtze River, among which the classical gardens of Suzhou are more famous for "Jiangnan gardens are the best in the world, and Suzhou gardens are the best in the south". Therefore, the classical gardens of Suzhou are selected as the microcosm of Chinese gardens, and the artificial aesthetic characteristics of the space constructed in the classical gardens are explored from a small perspective, which also provides an opportunity to seek the meeting point between modern space design and garden space aesthetics. The objectives of this research were:1) The horticultural concept of Suzhou gardens. 2) The value of man and nature in garden design. 3) The aesthetic value of Suzhou gardens and horticulture. The Humble Administrator's Garden in Suzhou was selected as the sample for data collection and research. The research results are as follows: 1) The horticultural concept of Suzhou gardens, whether in terms of architecture, furniture, cultural context, etc., is reflected in the role of humanistic thoughts, which not only destroys the rational existence of natural material relations, but also combines them with the richness of human inner thoughts. 2) The garden becomes an ideal place for harmonious coexistence between man and nature 3) The garden displays poetic and picturesque literary connotations, as well as philosophical and moral emotional Revelations. This aesthetic function gives the garden a deeper cultural connotation, making the garden not only a landscape, but also a rich literary language and spiritual comfort. In short, respect the traditional regional culture, explore the idea of space garden of Suzhou classical garden, Suzhou garden is not only the representative of ancient Chinese garden architecture, but also an important carrier of Chinese traditional culture. The preservation and inheritance of Suzhou gardens not only helps to protect China's cultural heritage, but also helps to promote the exchange and progress of human civilization.